Work Experience and Achievement: Their Influence on Lecturers’ Career - Hary Murcahyanto; Mohzana Mohzana; Muh Fahrurrozi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze the effect of work experience and work performance on lecturer careers. This study uses a quantitative method that examines three variables, namely two independent variables and one dependent variable. The independent variables are work experience and work performance, while the dependent variable is the lecturer's career (Y). This research was conducted using quantitative research with a survey method with a path analysis approach, with a total population of 160 lecturers and a sample of 60 people. The instrument test in this study used validity and reliability tests. Using path analysis and hypothesis testing. The results of the calculation of normality in the dependent variable work experience data (X1) the hypothesis is accepted or in other words the data is normally distributed. In the work performance data as the dependent variable (X2) the hypothesis is accepted or in other words the data is normally distributed. In the lecturer career data as an independent variable (Y) the hypothesis is accepted or in other words the data is normally distributed. In the linearity test, there is a linear relationship between the work experience variable (X1) and the work performance variable (X2) on the lecturer career variable (Y). The conclusion from this research is that there is an effect of work experience on the career of lecturers, there is an effect of work performance on the career of lecturers and there is an influence of work experience on the career of lecturers.